New evidence of a mitochondrial genetic background paradox: Impact of the J haplogroup on the A3243G mutation - Pennarun Erwann; Arveiler Benoit; Bellanne-Chantelot Christine; Feldmann Delphine; Rotig Agnes; Godinot Catherine; de Camaret Benedicte; Batandier Cécile; Allouche Stéphane; Martin-Négrier; Reynier Pascal; Amati-Bonneau Patricia; et al. (BMC, 2008)
Abstract Background The A3243G mutation in the tRNALeu gene (UUR), is one of the most common pathogenic mitochondrial DNA (mtDNA) mutations in France, and is associated with highly variable and heterogeneous disease phenotypes. To define the relationships between the A3243G mutation and mtDNA backgrounds, we determined the haplogroup affiliation of 142 unrelated French patients - diagnosed as carriers of the A3243G mutation - by control-region sequencing and RFLP survey of their mtDNAs. Results The analysis revealed 111 different haplotypes encompassing all European haplogroups, indicating that the 3243 site might be a mutational hot spot. However, contrary to previous findings, we observed a statistically significant underepresentation of the A3243G mutation on haplogroup J in patients (p = 0.01, OR = 0.26, C.I. 95%: 0.08-0.83), suggesting that might be due to a strong negative selection at the embryo or germ line stages. Conclusion Thus, our study supports the existence of mutational hotspot on mtDNA and a "haplogroup J paradox," a haplogroup that may increase the expression of mtDNA pathogenic mutations, but also be beneficial in certain environmental contexts.